THE INFLUENCE OF FALSIFICATING HISTORY ON HISTORICAL THINKING - Karimov Yuldosh (American Journal Of Social Sciences And Humanity Research, 2024)
The article examines the causes and consequences of falsification of history and its negative impact on historical thinking. It has been argued that a system based on colonialism and a single ideology is aimed at gaining public support by falsifying history with ulterior motives hidden behind it. It is also explained that the influence of falsification of history on the construction of social life through historical thinking can have disastrous consequences.